Distortion of the Magnetic Field at Paragon Bore, South Australia. Issue 1 (1st December 2019) - Foss, Clive; McKenzie, Blair; Katona, Laszlo
Summary: Magnetic field anomalies measured by the Gawler Craton Aeromagnetic Survey (GCAS) have revealed anomalies of amplitude > 18, 000 nT over Paragon Bore. The flying height is 60 metres above ground and depth to basement is 150 metres below ground, so the causative basement sources clearly have magnetizations of extreme intensity. We apply an iterative processing of the GCAS TMI data to a vector-consistent TMI. This also supplies vector component grids which we downward continue to the ground surface and then transform to declination and inclination maps. We invert the measured TMI using a model of multiple ellipsoids to enable inclusion of substantial self-demagnetization effects. Vector components forward computed from the inversion model at ground level are also transformed to declination and inclination maps which closely match those derived from the filter transform. Deviations of declination and inclination about the regional values are -15° to +21° and -14° to +5° respectively. High magnetic susceptibility values reported from borehole intersections (up to 1.6 SI in 2 boreholes) are mostly associated with banded iron formation (BIF) and metasomatic magnetite-rich rocks. These values are about 1/3rd of the equivalent inversion model intersection susceptibilities. We suggest that this apparent discrepancy is due to self-demagnetization effects in the susceptibility measurements and the presence of substantial (possibly viscous) remanent magnetization.